The Real Effect of Sociopolitical Racial/Ethnic Animus: Mutual Fund Manager Performance during AAPI Hate - Agarwal, Vikas; Jiang, Wei; Luo, Yuchen; Zou, Hong (Review of Financial Studies, 2026)
During the 2020–2021 “AAPI Hate,” mutual funds led by female managers perceived as East Asian underperformed relative to other female managers. This effect is stronger in states with higher anti-Asian animus, among more actively managed funds, and when these managers hold sole or senior roles. Factors concurrent with COVID-19, including childcare challenges, concerns for overseas families, marketplace and workplace discrimination, and exposure to the Chinese economy, cannot explain the effect. Underperformance is traceable to poor stock picking due to impairments in generating private information. Racial-ethnic animosity, even outside workplace or marketplace, hinders productivity and decision-making in high-skill professions.